2017
DOI: 10.1007/s00520-017-3912-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of family adaptability and cohesion on anxiety and depression of terminally ill cancer patients

Abstract: A higher family adaptability resulted in a lower degree of anxiety and depression in terminally ill cancer patients. The higher the family cohesion, the lower the degree of depression in the patient. The presence of the family caregiver and the visiting time by family and friends did not affect the patient's anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
4
27
0
2
Order By: Relevance
“…The results of our study showed that cohesion was significantly lower in the family of patients with MDD than in healthy families. Consistent with this study, the results of a study showed that the family had revers cohesion with the degree of depression in cancer patients (15). The results of another study showed that depression had a predictive role in family cohesion (20).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of our study showed that cohesion was significantly lower in the family of patients with MDD than in healthy families. Consistent with this study, the results of a study showed that the family had revers cohesion with the degree of depression in cancer patients (15). The results of another study showed that depression had a predictive role in family cohesion (20).…”
Section: Discussionsupporting
confidence: 76%
“…In Iran and even other countries, there is limited evidence on the effects of the presence of psychiatric patients on the family structure (12,15). For example, the results of a longitudinal study have shown that the presence of a patient with bipolar disorder reduces family cohesion (16).…”
Section: Introductionmentioning
confidence: 99%
“…The family environment can significantly predict the emergence of anxiety and depressive symptoms directly, which is consistent with previous results. For example, some studies found that there was a correlation between cohesion in the family environment and depression in family members ( Burnett et al, 2017 ); families with high cohesion, which have high levels of family support and ties, likely reduce depression ( Park et al, 2018 ; Cano et al, 2020 ). In contrast, low family cohesion and conflict between parents increased the risk of depression and anxiety in family members ( Park et al, 2018 ; Cano et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies found that there was a correlation between cohesion in the family environment and depression in family members ( Burnett et al, 2017 ); families with high cohesion, which have high levels of family support and ties, likely reduce depression ( Park et al, 2018 ; Cano et al, 2020 ). In contrast, low family cohesion and conflict between parents increased the risk of depression and anxiety in family members ( Park et al, 2018 ; Cano et al, 2020 ). In families with a high degree of cohesion, individuals can get more psychological help and emotional support within the family ( Birgisdóttir et al, 2019 ), so that the psychological pressure can be appropriately relieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation